An Author Topic Analysis of Tobacco Regulation Investigators - Li, Ding Cheng (AMIA Jt Summits Transl Sci Proc, 2014)
To facilitate the implementation of the Family Smoking Prevention and Tobacco Control Act of 2009, the Federal Drug Agency (FDA) Center for Tobacco Products (CTP) has identified research priorities under the umbrella of tobacco regulatory science (TRS). As a newly introduced field, the current landscape of TRS research is unclear. In this work, we conducted a bibliometric study of TRS research by applying author topic modeling on MEDLINE citations published by currently-funded TRS principle investigators. Our initial results show that author topic modeling can address the issue of research interests reasonably. Furthermore, a network involving authors, topics and words can be established for more detailed bibliometric analysis. This network may also be useful to grantees and funding administrators in suggesting potential collaborators or identifying those that share common research interests for data harmonization or other purposes.